Development of animal feed resources and the importance of agroforestry in relation to livestock production - Tothill, J.C. (Institute of Agricultural Research, 1991)
Reviews the work being conducted by ILCA in relation to the Development of agroforestry materials and their utilization in the typical mixed crop-livestock farming systems of Ethiopia; evaluates germplasm of multipurpose trees for a range of environments and identifies best-bet lines for improved feed resources, improved management of soil fertility, and other purposes such as fuelwood and wood resources; and develops methods of managing these resources in alley farming systems for improved livestock nutrition and soil fertility maintenance.